An Independent Auditor's Ex Post Criteria for the Disclosure of Information - Penno, Mark; Watts, John S. (Journal of Accounting Research, 1991)
Mark Penno, John S. Watts, An Independent Auditor's Ex Post Criteria for the Disclosure of Information, Journal of Accounting Research, Vol. 29, Studies on Accounting Institutions in Markets and Organizations (1991), pp. 194-212